ANALISIS BIAYA,VOLUME DAN LABA SEBAGAI ALAT PERENCANAAN LABA PADA HOTEL OMPU HERTI SEJAHTERA KABUPATEN TOBA SUMATERA UTARA - Joel Fernandes Silitonga; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The author in this study uses descriptive quantitative data analys method.The data collection technique used in the preparation of this thesis is the documentation study which is a data collection technique by studying documents related to research problems such as the company’s financial statements in the form of profit and loss in 2016-2020. From the data that has been calculated ysing the tools used in the profit vo,ume cost analysis,the planned profit target of Hotel Ompu Herti Sejahtera is expected to increase by 10% from the previous year,but based on the results,Hotel Ompu Herti has not been to able to achieve the target fully even though there are several years,namely 2016 and 2020 saw a significant increase in profit Keywords : Cost,Volume and Profit